Evaluating combined therapy with myoinositol and D-chiro-inositol in infertility management across PCOS phenotypes: a comprehensive retrospective data analysis - Ramaraju, Renuka Lalitha Naga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder affecting up to 20% of reproductive-aged women, often leading to infertility due to chronic anovulation. The condition has a multifactorial etiology involving genetic, hormonal, and metabolic factors, with insulin resistance being a key feature. The clinical presentation and therapeutic response can vary among different PCOS phenotypes. Myoinositol and D-chiro inositol has garnered attention as a potential insulin sensitizer with fertility-enhancing effects in women with PCOS. This study aimed to evaluate the impact of Myoinositol and D-chiro inositol treatment on fertility outcomes across different PCOS phenotypes, focusing on pregnancy rates and phenotype-specific responses. Methods: A review of medical records from 200 women with PCOS treated at M2M Women’s Clinic between 2018 and 2020 was conducted. Each woman took a sachet twice daily containing 2 g of Myo-Inositol and 50 mg of D-Chiro-Inositol in a 40:1 ratio. They were grouped into four types (A, B, C, D) based on the Rotterdam criteria. Data on treatment specifics, fertility outcomes, and follow-up results were analysed, and Chi-square tests were employed to compare pregnancy rates across the phenotypes. Results: Out of the 200 participants, 143 (71.5%) completed follow-up. The overall pregnancy rate was 70.6%, with rates of 70.4% in Phenotype A and 69.1% in Phenotype D. Phenotypes B and C achieved 100% conception rates; however, these findings were constrained by small sample sizes. Conclusions: Myoinositol, in combination with D-Chiro-Inositol in the physiological 40:1 ratio, appears effective in improving fertility outcomes, particularly in Phenotypes A and D. Further research with larger sample sizes is warranted to validate these findings across all PCOS phenotypes and refine phenotype-specific treatment protocols.